1994
DOI: 10.2172/10196541
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocyanide safety project task 3 ferrocyanide aging studies FY 1994 annual report

Abstract: This annual report gives the results of the work conducted by the Pacific Northwest Laboratory in FY 1994 on Task 3 of the Ferrocyanide Safety Project, Ferrocyanide Aging Studies. Waste aging refers to the dissolution and hydrolysis of simulated Hanford ferrocyanide waste in alkaline aqueous solutions by radiolytic and chemical means. The ferrocyanide simulant primarily used in these studies Savannah River Operations Office PO. Box A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Recent aging studies of ferrocyanide waste show that the combined effects of temperature, radiation, and pH during 38 years or more of storage would have destroyed most of the ferrocyanide originally added to the tanks (Babad et al 1993;Lilga et al 1993Lilga et al , 1994Lilga et al , 1995Lilga et al and 1996. This prediction has been confirmed by the tank samples analyzed to date.…”
Section: Ferrocyanide Degradationmentioning
confidence: 84%
“…Recent aging studies of ferrocyanide waste show that the combined effects of temperature, radiation, and pH during 38 years or more of storage would have destroyed most of the ferrocyanide originally added to the tanks (Babad et al 1993;Lilga et al 1993Lilga et al , 1994Lilga et al , 1995Lilga et al and 1996. This prediction has been confirmed by the tank samples analyzed to date.…”
Section: Ferrocyanide Degradationmentioning
confidence: 84%
“…3 and 4). Other aspects of alkali metal nickel ferrocyanide solubility, including the insolubility of the cesium-containing materials, and hydrolysis have been described in previous reports (Lilga et al , 1993(Lilga et al , 1994. In addition, mechanisms of contacting deep sludges layers with caustic have been discussed (McGrail et al 1993;McGrail 1994).…”
Section: Work Accomplishedmentioning
confidence: 92%
“…The results of Aging Studies will directly assist in determining which strategy will ensure safe storage of the ferrocyanide waste in the tanks and how the ferrocyanide safety issue can be resolved. In previous ferrocyanide waste aging studies utilizing flowsheet simulants (Lilga et al , 1993(Lilga et al , 1994, redissolution of Na,NiFe(CN), in caustic solutions was shown to occur and was studied under a variety of conditions. Products of the dissolution are soluble Fe(CN)64 and insoluble Ni(0HX.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…A literature search revealed work that indicated that sodium nickel ferrocyanide decomposed (aged) to lower energy compounds when exposed to a typical Hanford Site tank environment (Babad et al 1993). Studies with waste simulants corroborate that ferrocyanide decomposes under waste tank conditions (Lilga et al 1993(Lilga et al , 1994(Lilga et al , and 1995. Three parameters (temperature, exposure to high pH, and radiation dose) strongly affect the rate of decomposition.…”
Section: Ferrocyanide Aging (Question #1)mentioning
confidence: 99%